Legal Analysis of Child Sexual Abuse through Grooming: A Study of Rokan Hilir District Court Decision Number 410/Pid.Sus/2025/PN Rhl - Sophian Parbue Simamora; Risdalina Risdalina; Kusno Kusno (SIGn Jurnal Hukum, 2026)
The phenomenon of child sexual offenses disguised behind a romantic narrative or dating constitutes a serious challenge for law enforcement in Indonesia. The child’s consent is frequently misinterpreted as grounds for abolishing the penalty in such cases. This research aims to analyze the legal construction in Decision Number 410/Pid.Sus/2025/PN Rhl. The decision penalizes the perpetrator of child sexual intercourse although the Child Victim actively lied to their parents in order to meet the perpetrator. This research employs a normative legal research method through the statute and case approaches. This research examines the judicial interpretation regarding the grooming element and the application of the voortgezette handeling doctrine in sentencing. The analysis results indicate that the judge progressively constructed the promise of marriage as a form of deceit that paralyzes the child’s critical reasoning. Therefore, the given consent is deemed vitiated. However, this research also found a gap in substantive justice due to the absence of restitution imposed on the Defendant. This reflects the persisting strength of the retributive paradigm compared to the restorative paradigm within the juvenile criminal justice system. It is concluded that although a custodial sentence was imposed, the state failed to execute its constitutional obligation to comprehensively restore the rights of the victim. This research recommends a reform of the prosecution paradigm in which the Prosecutor and the Judge actively demand and adjudicate restitution ex officio. Furthermore, integrating a victim impact statement is essential to accurately assess the victim’s actual damages and achieve comprehensive justice.